The Bergen proton CT system - Aehle, Max; Seco, Joao; Volz, Lennart (Journal of Instrumentation, 2023)
The Bergen proton Computed Tomography (pCT) is a prototype detector under construction. It aims to have the capability to track and measure ions’ energy deposition to minimize uncertainty in proton treatment planning. It is a high granularity digital tracking calorimeter, where the first two layers will act as tracking layers to obtain positional information of the incoming particle. The remainder of the detector will act as a calorimeter. Beam tests have been performed with multiple beams. These tests have shown that the ALPIDE chip sensor can measure the deposited energy, making it possible for the sensors to distinguish between the tracks in the Digital Tracking Calorimeter (DTC).
Online veröffentlicht am 23. Februar 2023
Gesehen am 23.11.2023